Effect of Prolonged Intermittent Fasting in Ramadan on Biochemical and Inflammatory Parameters of Healthy Men - Fatemeh Mohammadzade; Mohammad Ali Vakili; Alireza Seyediniaki; Saeed Amirkhanloo; Mehran Farajolahi; Hamideh Akbari; Samira Eshghinia (Golestan University Of Medical Sciences, 2017)
ABSTRACT Introduction: Ramadan is an Islamic month during which Muslims abstain from eating, drinking and smoking from dawn to sunset. Ramadan is a model of prolonged intermittent fasting. Previous studies have shown that fasting has beneficial effects on human health. However, the results of these studies have been inconsistent. The aim of present study was to investigate the effect of fasting during Ramadan on biochemical parameters and inflammatory markers. Materials and Methods: This prospective observational study was conducted in July 2013. Thirty healthy men who were fasting during Ramadan were enrolled in the study. Anthropometric measurements were taken from each subject. Fasting venous blood samples were taken one week before Ramadan, during the last week of Ramadan and four weeks after Ramadan. Serum interleukin-6, high sensitivity C-reactive protein, fasting blood sugar (FBS), insulin, total cholesterol, triglycerides, low-density lipoprotein and high-density lipoprotein levels were measured. Results: No significant change was observed in serum total cholesterol, systolic and diastolic blood pressure, interleukin-6 and high sensitivity C-reactive protein. Fasting in Ramadan significantly decreased body mass index (P< 0.0001), FBS (P< 0.0001), triglycerides (P< 0.01), erythrocyte sedimentation rate (P< 0.01), insulin (P< 0.02), HOMA index (P< 0.001) and high-density lipoprotein-cholesterol (P < 0.0001). Conclusions: This study indicates that fasting during Ramadan has some positive effects on body mass index, serum triglycerides, high-density lipoprotein, FBS, insulin and HOMA index. KEYWORDS: Ramadan, Fasting, C-reactive protein, blood glucose, High-density lipoprotein